Empirical Study of Measures to Accelerate the Rural Economy: Potential for Nature Tourism in the Bukit Rimbang Bukit Baling Wildlife Reserve in Riau Province - Adrian Novendra; Almasdi Syahza; Ando Fahda Aulia (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan)
The Bukit Rimbang Bukit Baling Wildlife Reserve has unique species and diverse animals whose populations and habitats need to be protected. The location of the reserve also serves as a source of water for the community and prevents floods, landslides, and erosion. Before designation as a wildlife reserve, the forest served as a source of livelihood in the community, which helped manage and preserve conservation areas. The selected respondents were 35 heads of families, Information was obtained using the participatory rural appraisal (PRA) approach. The PRA results were tabulated and an estimate of willingness to pay for environmental ecosystem services was calculated. The economic value was calculated by summing up all the benefits identified from the ecosystem and the commodities utilized. This study aimed to determine the valuation of use and economic value based on non-use value. The results showed that the wildlife reserve area has the potential for economic value that may benefit the surrounding community and create environmental balance through river utilization and using non-timber forest products. There is increased income level, occupation, and environmental quality. Moreover, the potential use of non-timber forest products is an economic alternative to the community. The area has the potential to develop natural tourism as a learning process for future generations.